SISTEM PAKAR MENENTUKAN JENIS GANGGUAN PERKEMBANGAN ANAK MENGGUNAKAN METODE CERTAINTY FACTOR - Waruwu, Resana Triani; Sinaga, Anita Sindar RM (ScientiCO : Computer Science and Informatics Journal, 2019)
The age of the child until the age of 10 years is a period of children can absorb and learn all the information obtained quickly. Children developmental disorders can be seen from the way they behave, interact and from daily communication. System analysis activities to observe certain and uncertain events, then document the needs that will be met in the new system. The system that is built is capable of performing calculations for diagnosing disorders in child development using the certainty factor method. The system displays the results of the diagnosis of child development, presentation of the level of confidence in the results of the diagnosis and can display control of the types of developmental disorders in children. Users who have been identified who can use this expert system are general users, users who can diagnose a child's developmental disorders and can see the results of the diagnosis.